Resolution of international banks: can smaller countries cope? - Dirk Schoenmaker (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
The stability of a banking system ultimately depends on the strength and credibility of the fiscal backstop. While large countries can still afford to resolve large global banks on their own, small and medium-sized countries face a policy choice. This paper investigates the impact of resolution on banking structure. The financial trilemma model indicates that smaller countries can either conduct joint supervision and resolution of their global banks (based on single point of entry resolution) or reduce the size of their global banks and move to separate resolution of these banks' national subsidiaries (based on multiple point of entry resolution). Euro-area countries are heading for joint resolution based on burden sharing, while the UK and Switzerland have implemented policies to downsize their banks.
Keywords: F30; G21; G28; 330; Global Financial Architecture; International Banks; Burden Sharing; Resolution Planning; Single Point of Entry; Multiple Point of Entry